Carry-over effects on bud fertility makes early defoliation a risky crop-regulating practice in Mediterranean vineyards - Lopes, C.M. (2020)
Background and Aims: Recently, early defoliation (ED) has been used widely to regulate yield and reduce bunch compactness to improve tolerance to bunch rot. The aim of this study was to test ED, as an alternative to the conventional crop thinning (CT), to regulate yield and improve tolerance to bunch rot of the Vitis vinifera L. cv. Aragonez. Methods and Results: Early defoliation and CT were compared with an untreated Control over three consecutive seasons in a commercial vineyard in Portugal. Early defoliation had little effect on tolerance to bunch rot and led to progressive loss of yield reducing fruitset, bunch number, berry number and mass, compared to Control vines. Reduced bunch number is likely to be a function of reduced bud fertility. Crop thinning also reduced yield but, unlike ED, the yield reduction was less and remained constant over the seasons studied. Both ED and CT had little effect on berry composition. Conclusions: Among the two crop-regulating techniques, CT appears more suitable than ED to control grape yields in regions where yield limitations are imposed. The progressive yield decline caused by ED is likely to be not economically viable in the region studied. Significance of the Study: Early defoliation reduces bud fertility in unirrigated vineyards under Mediterranean conditions. Therefore, this practice should be avoided under those conditions